A necrópole medieval do Mosteiro de S. Miguel de Refojos, Cabeceiras de Basto - Queiroga, Francisco Reimão (2021)
As a measure of previous evaluation for the project of remodelling of the cloister garden of the Monastery of S. Miguel de Refojos, in Cabeceiras de Basto, an archaeological excavation was required, in the course of which a number of human graves was uncovered. This is a portion of a cemetery presumably located outside of a church from an earlier phase of the monastery, which was superposed by the later phase cloister that is still standing. The cemetery is dated between the XII-XIII to the XVIIth centuries. The excavation of the cemetery has yielded remains of 35 burials, amongst male and female individuals, in addition to one pit where a canine burial was performed in a time and circumstances as yet undetermined